THE IMPACT OF LIQUIDITY, LEVERAGE, AND CAPITAL INTENSITY ON TAX AVOIDANCE IN MANUFACTURING COMPANIES (2022-2024) - Sasmita, Anggi; Fionasari, Dwi; Fitriana, Nur (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
This study aims to determine the effect of liquidity, leverage, and capital intensity on tax avoidance. This is a quantitative research. The data used in this study is secondary data. The population in this study consists of 47 companies, and the sample includes 28 companies over three years. The sampling technique used is purposive sampling. The total research sample is 84 financial statements and annual reports from manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange (IDX) during the period 2022-2024. The data obtained is processed using SPSS 25 with multiple linear regression testing. The results of this study show that liquidity and leverage have no effect on tax avoidance, while capital intensity affects tax avoidance.